Answer:
679.1N
Step-by-step explanation:
Assuming equation 3 is Newton's universal law of gravity:
[tex]F_g = G\frac{m_1m_2}{d^2}[/tex]
Where G is the universal gravity constant:
[tex]G=6.673 x10^{-11}\frac{Nm^2}{kg^2}[/tex]
You need to express the radius of earth in m:
[tex]3959mi*\frac{1609m}{1mi}=6.370*10^6m[/tex]
If you weight 70Kg, just replace the values in the equation:
[tex]F_g = 6.673 *10^{-11}*\frac{70*5.900*10^{24}}{(6.370*10^6)^2}= 6.673 *10^{-11}*\frac{4.13*10^{26}}{4.058*10^{13}}=\\6.673*10^{-11}*1.018*10^{13}= 679.1N[/tex]